Paper towns - Green, John 1977- (New York Speak, 2008)
One month before graduating from his Central Florida high school, Quentin "Q" Jacobsen basks in the predictable boringness of his life until the beautiful and exciting Margo Roth Spiegelman, Q's neighbor and classmate, takes him on a midnight adventure and then mysteriously disappears
1
NEW, LITERATURE
Keywords: Coming of age -- Fiction; Missing persons -- Fiction; Mystery and detective stories; Florida -- Fiction